Mainstream cigarette smoke induces autophagy and promotes apoptosis in oral mucosal epithelial cells. (March 2020) - Liu, Qin; Zhao, Maomao; Chen, Wei; Xu, Kaiyuan; Huang, Fan; Qu, Junxing; Xu, Zhen; Wang, Xiang; Wang, Yong; Zhu, Yanan; Wang, Wenmei
Highlights: Cigarette smoke can simultaneously activate autophagy and apoptosis in mouse and human oral epithelial cells. Autophagy inhibition can aggravate the CSE-triggered apoptosis of oral epithelial cells. Autophagy induction can inhibit the CSE-triggered apoptosis of oral epithelial cells. Abstract: Objective: This study aimed to investigate the effects of cigarette smoke (extract) on autophagy and apoptosis in oral mucosa epithelial cells. Methods: The effects of cigarette smoke extract (CSE) on autophagy and apoptosis in oral epithelial cells were studied in vivo and in vitro. Leuk-1 cells were administered cigarette smoke extract or chloroquine (CQ) and rapamycin (RAPA) at different concentrations. Immunoblotting, immunofluorescence, Western blotting and flow cytometry were used to detect autophagy-related protein and apoptosis levels, screen the optimal concentration and stimulation time, and verify the effect of CSE stimulation on autophagy and apoptosis in leuk-1 cells. Meanwhile, autophagy expression in epithelial cells from the local oral tissues of mice who had smoked for 5 months was detected. Results: Under CS stimulation, LC3-II and Beclin-1, the key proteins of leuk-1 autophagy, were upregulated in a concentration- and time-dependent manner. In addition, CS significantly upregulated the expression of Cleaved caspase-3 (C-casp3), a protein involved in apoptosis. However, under stimulation with CQ, autophagy in leuk-1 cells was inhibited and the level of C-casp3 and the apoptosis rate were increased. The autophagy activator RAPA significantly reduced the level of C-casp3 and apoptosis rate in leuk-1 cells. Conclusion: The results of this study indicate that CS can simultaneously activate autophagy and apoptosis in mouse and human oral epithelial cells, that autophagy inhibition can aggravate the CSE-triggered apoptosis of oral epithelial cells, and that autophagy induction can inhibit the CSE-triggered apoptosis of oral epithelial cells. Autophagy is suggested to play a protective role in the CSE-induced apoptosis of oral epithelial cells. Further studies are needed to explore the concrete mechanisms underlying the regulatory effects of CS-induced apoptosis and to gain in-depth insight into the complex interactions between apoptosis and autophagy.